Proposta de classificação acústica de habitações brasileiras baseadas na percepção dos usuários - Lourenço, Willian Magalhães de (2023)
The growth and verticalization of cities have caused significant changes in construction methods and materials that directly impact architectural acoustics. Buildings must, due to their primary function, guarantee habitability and quality of life for users, with acoustic comfort being one of the factors that is included in this demand. However, the acoustic performance levels required by the regulations that regulate Brazilian civil construction do not necessarily guarantee the acoustic quality and comfort of users of residential buildings. The present work aims to propose an acoustic classification method for residential buildings in Brazil, based on the acoustic performance of flooring systems, internal and external vertical seals and noise from building and sanitary installations and equipment, based on the perception of users. . The method developed evaluates three components: the context (the environmental integration of the building, which influences the quality of the internal environment), the building (architectural design issues that guarantee better acoustic conditions in spaces, common access, circulation, among others) and housing (performance of construction systems), through a questionnaire, applied to the Brazilian population, measuring discomfort and priorities in terms of sound insulation from the perception of Brazilians. It was applied in three case studies, two buildings in the city of Santa Maria, multifamily, one made of reinforced concrete, the other made of structural masonry, and a third study based on bibliographical references (performance through research), demonstrating that it is possible Also use the tool in design stages before execution. Therefore, with the evaluation of the three components, a global acoustic evaluation of each building can be drawn up, with the aim of applying the labeling of the acoustic quality of housing units, promoting housing quality and introducing a new market valuation parameter.